The subjects of literary and artistic copyright - Bonadio, Enrico; Sappa, Cristiana (Edward Elgar Publishing, 2022)
"This accessible and innovative book examines to what extent copyright protects a range of subjects who are engaged in the creation and management of literary and artistic works, and how such subjects use copyright to protect their interests. Offering a complementary analysis, The Subjects of Literary and Artistic Copyright explores how copyright regulates the production and management of literature and art. The book examines the creators of literature and art, as well as market operators such as publishers and "managers" including museums, galleries, and universities. The perspectives offered cover a diverse range of subjects, and confront the regular contradictions and conflicts that occur within literary and artistic copyright interests. The chapters illustrate, via historical and empirical analysis, that established practices and traditional approaches to the management of copyright need to be revisited, in order to be more aligned with current social and technological frameworks. Providing a starting point for future research paths on copyright practices in art and literature, this insightful book will be of interest to legal academics looking to expand their knowledge of literary and artistic copyright. Law professionals with interests in intellectual property and art law will also benefit from its novel approach"--